The impact of playing tennis on the organ of vision - threats, benefits and prevention of the organ of vision - Dominik Rabstein; Piotr Gościniewicz; Hanna Porwolik; Agata Porwolik; Patrycja Pabis; Agnieszka Porwolik; Magdalena Bodera; Radosław Szydłowski (Journal of Education, Health and Sport)
This paper examines the impact of playing tennis on the visual system, providing an in-depth analysis of physiological, adaptive, and risk-related aspects associated with the sport. The dynamic nature of tennis necessitates intensive visual engagement to track a fast-moving ball, thereby enhancing dynamic vision, depth perception, and visuomotor coordination. On the other hand, the sport also poses risks such as eye strain and mechanical injuries, including corneal and retinal damage.